Challenges Perceived by Para – vets in Varanasi District for Delivery of Animal Health Services - Shelly Sharma; K.S. Kadian; H.R. Meena (The Indian Veterinary Journal, 2024)
The field survey was conducted in the Varanasi district to find out thechallenges perceived by para-vets and for this a total of 40 para-vets were selected and interviewed throughout November 2021 to April 2022. The data were collected through semi – structured interview schedule and analysed with appropriate statistical tools. The challenges perceived by paravets were identified in four basic categories such as technical challenges, administrative challenges, Information and Communications Technology tools challenges and personal challenges. Among technical challenges, lack of availability of liquid nitrogen on time was ranked I, poor adoption of animal husbandry innovation was ranked II and inadequate policies and regulation was ranked III according to the score obtained in Garrett ranking. For administrative challenges, lack of monitoring, reporting and documentation from V.O/ C.V.O to assess the performance in the field was ranked I, poor networking with other Institutions was ranked II and lack of clear policy and procedures was ranked III. Challenges perceived in using ICT tools were ignorance in use of mobile app related to veterinary services (I), unavailability of veterinary related information through ICT (II) and lack of updating of tools or apps (III). The major personal challenges perceived by para-vets were no provision of life insurance to the para-vets while handling the high risk cases which was ranked I, inadequate transport facilities was ranked II and lack of access to loan facilities or credit was ranked III.